Fe‐Co‐Ni/Nitrogen‐Doped Mesoporous Carbon Materials for Electrochemical Oxygen Reduction. Issue 45 (5th December 2018) - Qiu, Shujun; Gao, Wei; Peng, Hongliang; Chu, Hailiang; Li, Zehao; Liang, Huanbiao; Zou, Yongjin; Xiang, Cuili; Zhang, Huanzhi; Yan, Erhu; Xu, Fen; Sun, Lixian; et al.
Abstract: Recently, simultaneous doping of transition metals and heteroatoms in carbonaceous materials has become promising alternatives to Pt‐based catalysts for electrochemical oxygen reduction reaction (ORR). In this study, a kind of Fe‐Co‐Ni/N‐doped carbon framework catalysts is successfully synthesized using a hard template of SBA‐16@graphene oxide (SBA‐16@GO), during which ferroporphyrin is used as a nitrogen source and triblock copolymer Pluronic F127 is used as surfactant. The as‐prepared catalysts exhibit unique porous structure with high specific surface area (853 m 2 g −1 ) and the average pore size distribution in the range of 2.4 to 3.3 nm, which offers short diffusion channels for the penetration and transportation of electrolyte. Moreover, the sample pyrolyzed at 800 °C (Fe‐Co‐Ni/NPC‐800) exhibits enhanced electrocatalytic activity with the half‐wave potential (E1/2 ) of ∼ −0.09 V, which is only negatively shifted by about 50 mV for ORR in alkaline electrolyte compared to the commercial Pt/C catalyst. Abstract : A kind of Fe‐Co‐Ni/N‐doped carbon framework catalyst is successfully synthesized through a hard template of SBA‐16@graphene oxide (SBA‐16@GO) and the following calcination, which exhibits enhanced electrocatalytic activity for ORR in alkaline medium.